Effect of drying methods on the free radicals scavenging activity of Vernonia amygdalina growing in Malaysia - Alara, Oluwaseun Ruth; Nour, A. H.; Siti Kholijah, Abdul Mudalip; Olalere, Olusegun Abayomi (King Saud University, 2017)
The extracts from Vernonia amygdalina leaves dried using different modes of drying were examined for their antioxidant activities. The component identification was carried out on extract with the highest antioxidant property using GC–MS analysis. Using DPPH, ABTS+ and H2O2 radical scavenging assays, the shade, the sun, oven at 40, 50, and 60 °C dried sample extracts were screened. The obtained scavenging activities were in the order: shade drying > sun drying > oven drying at 40 °C > oven drying at 50 °C > oven drying at 60 °C. The extract from shade-dried sample exhibited the highest activity by scavenging 63.21–92.25% of DPPH, 75.32–93.15% of ABTS+ , and 82.53–95.78% of H2O2 radicals, which were higher than those of ascorbic and gallic acid scavenging activities. In addition, the effects of drying methods and extract concentrations on the antioxidant activity of V. amygdalina leaf were significant (p < 0.05). A total number of 11 major compounds were identified from the shade-dried extract viz: phytol (43.69%), (z,z,z)-methyl ester-9,12,15-octadecatrienoic acid (17.60%), 2-methyl-3-hexanol (6.83%), ethyl ester-9,12-octadecadienoic acid (6.07%), ethyl ester linoleic acid (5.19%), ethyl ester hexadecanoic acid (5.06), heneicosane (4.15%), heptacosane (3.25%), and others are less than 3%. Therefore, it can be deduced that an increase in drying temperature may deteriorate the antioxidant activity of Vernonia amygdalina leaf.